STRATEGI PENGEMBANGAN WISATA DI PULAU BAWEAN KABUPATEN GRESIK - Mohammad Ramli; E.K.S Harini Muntasib; Agus Priyono Kartono (Media Konservasi, 2012)
Bawean island has many potential tourism objects both in the land and in the sea. There is a nature reserve and a sanctuary in the island where Bawean Deer an endemic species of Bawean Island lived. The development of bawean as a tourism destination was base on the natural resources culture, local management, local community and visitor characteristics.  The data was analyzed using SWOT (Strengths, Weaknesses, Opportunities and Threats) analysis, AHP (Analytical Hierarchy Process) and descriptive analysis.SWOT Analysis showed that the score of Strengths was 2,530; Weaknesses was 0,773; Opportunities was 1,15 and Threats was 1,89. The tourism objects development priority were 0,233 of gili and noko island; 0,220 of kastoba lake; 0,206 of bawean deer; 0,114 of pasir putih beach; 0,097 of slayar beach; 0,076 of waterfalls and 0,054 of hot spring.    Keywords: Bawean, tourism, SWOT, AHP